The social power of algorithms / edited by David Beer. - Beer, David, 1977- (Routledge, 2020)
The vast circulations of mobile devices, sensors and data mean that the social world is now defined by a complex interweaving of human and machine agency. Key to this is the growing power of algorithms - the decision-making parts of code - in our software dense and data rich environments. Algorithms can shape how we are retreated, what we know, who we connect with and what we encounter, and they present us with some important questions about how society operates and how we understand it. This book offers a series of concepts, approaches and ideas for understanding the relations between algorithms and power.